(untitled) (Iranian Journal of Kidney Diseases, 2012)
Almost all kidney transplant recipients with diabetes mellitus will eventually develop recurrence of diabetic nephropathy in their allograft. Despite this high incidence, there are very few reported cases of diabetic nephropathy of diffuse type, and the nodular sclerosis form is uncommon. Recurrence of diabetic nephropathy of nodular glomerulosclerosis type usually occurs during the second decade of transplantation. We report a rare case of diabetic nodular glomerulosclerosis developing 5 years after transplantation, leading to progressive kidney dysfunction and graft loss.